IMPLEMENTATION OF TAHFIDZ ALQURAN LEARNING PADANG ISLAMIC BOARDING SCHOOL - Sukrisman, Sukrisman; Kosim, Muhammad; Syafruddin, Syafruddin (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2023)
This research is motivated by facts that show there is great attention to learning tahfidz Alquran in formal, non-formal and informal education channels. Various efforts have been made to produce memorizers of the Koran so that some have made learning tahfidz of the Alquran a superior or mandatory extracurricular program, namely at the Ar-Risalah Islamic College and the Minangkabau Islamic Boarding School, Padang. The aim of this research is to determine the learning strategy for tahfidz Alquran in the aspects of learning planning, implementation of learning and evaluation of tahfidz Alquran learning at the Padang Islamic boarding school. This research was successful in finding i) Planning for Alquran tahfidz learning at the Ar-Risalah Islamic Boarding School and the Minangkabau Islamic Boarding School in Padang, namely the formulation of learning objectives, preparation of students, preparation of teaching staff, preparation of materials, methods, media and learning resources and the environment. ii) Implementation of Alquran tahfidz learning at the Ar-Risalah Islamic Boarding School and Minangkabau Islamic Boarding School, namely the implementation of learning objectives as evidenced by the seriousness of students, the arrangement of materials, methods, use of media and learning resources in accordance with the conditions of the learning environment. iii) Evaluation of Alquran tahfidz learning at the Ar-Risalah Islamic Boarding School and Minangkabau Islamic Boarding School is carried out by means of formative evaluation, namely at the end of the semester and the end of the year, summative evaluation is carried out at the end of the semester and the end of the year. every meeting and reporting of learning outcomes at the end of each year.